2019
DOI: 10.1017/s1368980019003513
|View full text |Cite
|
Sign up to set email alerts
|

Excessive gestational weight gain in the first trimester is associated with risk of gestational diabetes mellitus: a prospective study from Southwest China

Abstract: Objective:To evaluate the effects of gestational weight gain (GWG) in the first trimester (GWG-F) and the rate of gestational weight gain in the second trimester (RGWG-S) on gestational diabetes mellitus (GDM), exploring the optimal GWG ranges for the avoidance of GDM in Chinese women.Design:A population-based prospective study was conducted. Gestational weight was measured regularly in every antenatal visit and assessed by the Institute of Medicine (IOM) criteria (2009). GDM was assessed with the 75-g, 2-h or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Conversely, women who didn't diagnosed with gestational diabetes mellitus may be less likely to follow a diet or exercise, which could lead to more weight gain. This result was similar to the ndings of domestic and foreign academics [15,16] .In addition, it has been reported [17] that excessive weight gain in rst trimester was relative to an increased risk of gestational diabetes mellitus, regardless of pre-pregnancy weight. We did not make a consideration of weight gain in rst trimester, thus it may lead to an inconsistency between our ndings and those of some studies [18] .This also suggested that we should not neglect weight management in rst trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, women who didn't diagnosed with gestational diabetes mellitus may be less likely to follow a diet or exercise, which could lead to more weight gain. This result was similar to the ndings of domestic and foreign academics [15,16] .In addition, it has been reported [17] that excessive weight gain in rst trimester was relative to an increased risk of gestational diabetes mellitus, regardless of pre-pregnancy weight. We did not make a consideration of weight gain in rst trimester, thus it may lead to an inconsistency between our ndings and those of some studies [18] .This also suggested that we should not neglect weight management in rst trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with lower rate of gestational weight gain (less than 0.28 kg per week), a rate of weight gain of 0.28 kg per week or more was associated with an increased risk of GDM (OR = 2.03, 95% CI: 1.15-3.59) according to a study conducted in Peking University First Hospital in China [38]. Another prospective study from Southwest China showed that gestational weight gain in the first trimester above IOM recommendations increased the risk of GDM among underweight (OR = 2.50, 95% CI: 1.11-5.66), normal-weight (OR = 1.40, 95% CI: 1.02-1.91), and overweight/obese women (OR = 3.02, 95% CI: 1.12-8.14) compared with those within IOM recommendations, which indicated that excessive gestational weight gain in the first trimester is associated with increased risk of GDM regardless of pre-pregnancy BMI [51].…”
Section: Excessive Gestational Weight Gainmentioning
confidence: 94%
“…This result is 1•3 times higher than in a population of pregnant women without SARS-CoV-2 in Japan, where 2•7% were diagnosed with gestational diabetes [33]. Prior literature has established a relationship between elevated BMI and gestational weight gain on the presence of gestational diabetes; however, lack of reporting on BMI in women with gestational diabetes in this review inhibits us from inferring the same in SARS-CoV-2 positive pregnant women [34,35].…”
Section: Discussionmentioning
confidence: 59%